Liquidity, Solvency, and Activity on Profitability with Capital Structure as a Mediating in Green Industry Companies - Pradana, Yoga; Nadhiroh, Umi (Universitas Kadiri, 2025)
The purpose of this study is to determine the impact of liquidity, solvency, and activity on profitability using the capital structure as a mediating variable for companies in the green industry listed on the Indonesian Stock Exchange for the years 2021–2024.Purposive sampling and a quantitative approach were used to choose eight organizations as research samples. Three different kinds of variables are used in this study: independent, mediating, and dependent variables. The author analyzed data using SPSS software Multiple linear regression, conventional assumption tests, and the Sobel test were used to evaluate secondary data in the form of financial reports in order to look into the mediating role of capital structure. The findings indicate that while solvency and activity have a large beneficial impact on profitability, liquidity has no discernible influence. Profitability is not directly impacted by capital structure, but it is somewhat mediated by solvency.The findings show that although solvency and activity have a large positive impact on profitability, liquidity does not have a significant effect. Profitability is not directly affected by capital structure, but structure is able to mediate the effect of solvency on profitability, while the liquidity ratio and activity on profitability are not mediated by capital structure.